Transducers for the determination of the pressure and shear stress distribution at the stump-socket interface of trans-tibial amputees - Abu Osman, Noor Azuan; Spence, W.D.; Solomonidis, S.E.; Paul, J.P.; Weir, A.M. (2010)
Recent developments in prosthetic socket design have created renewed interest in monitoring the stress distribution at the socket-residual limb interface. Although a few devices for measuring pressure can be found in the literature, none are capable of measuring reliably in areas of high curvature, such as the important area at the patellar tendon bar. Furthermore, few devices can record shear stress, thought to be critical in causing tissue damage. In order to address these issues two new transducers have been designed and evaluated. One design allows the simultaneous recording of the normal and shear stresses at various points of the socket walls, while the other is capable of measuring the three components of the force applied on the patellar tendon. The latter design incorporates a feature that permits displacement of the patellar tendon bar, in order to study the effect of various amounts of indentation of the tendon on the stress distribution around the residual limb. Both transducers were calibrated using dead weights and special jigs to ensure accurate loading conditions. Under laboratory bench conditions the normal-shear force transducer showed: 2.03 per cent full scale output (FSO) hysteresis error for shear stress direction, 1.65 per cent FSO for normal direction; 99.56 per cent FSO overall accuracy for shear direction, and within 99.64 per cent FSO for normal direction; and for the patellar tendon transducer 1.53 per cent FSO hysteresis error for shear direction, 1.85 per cent FSO for shear stress direction; 99.65 per cent FSO overall accuracy for shear direction, and 99.58 per cent FSO for normal direction. During an amputee walking trial the transducers showed 92 per cent to 97 per cent repeatability. The two new transducers were used in conjunction with two other types of transducers, previously designed at the University of Strathclyde, in a series of tests on ten trans-tibial amputees. Sample results for walking activities and a summary of maximum stresses recorded are presented.